Uma proposta para o ensino de conceitos da fisica moderna por meio da aprendizagem baseada em problemas - Gonçalves, Karen Magno (2020)
The teaching of Modern Physics (MF) in high school classes has been a subject discussed by many teachers and researchers in recent years. It is a question about how we can insert MF teaching in schools and also how we can make students more active and interested in their learning. In order to solve this problem, we propose the construction and use of a Potentially Significant Teaching Unit (PSTU) based on Moreira, which uses, in its stages, the teaching strategy of Problem Based Learning (PBL), in order to investigate that aspects a didactic proposal that uses this teaching strategy can contribute to promote meaningful learning of MF concepts for students of the 3rd year of high school. Thus, as a methodology we use the qualitative approach and the epistemological basis of action research of the strategic type, which performs only one cycle in the application (planning → action → reflection → research → reframing). In addition, the data collection instruments were observation, problem solving, evaluative activity (use of scores) and questionnaires. Inserting the seven jumps proposed by Schmidt for PBL, we built the PSTU, which has eight steps, namely: (1) problem planning and formulation; (2) presentation of the problem and identification of previous knowledge; (3) brainstorming and preparation for studies; (4) addressing general knowledge through themes for individual studies; (5) increasing complexity and conducting new individual studies; (6) increased complexity and presentation of the problem solution; (7) carrying out an evaluative activity; (8) assessing the success of PSTU. After the implementation of the proposal and the analysis of the results obtained, it was noted that, in terms of student engagement in learning activities, there was an active collective participation and an increase in the progressive differentiations of the MF concepts during the orientation classes. In addition, this PSTU, in order to provide students with a cognitively demanding and communicational material, which at the same time favored meaningful learning, served as a basis for the construction of an educational product in the form of a didactic guide. Finally, it can be said that this PSTU, which made use of PBL as a teaching strategy, made it possible for students to actively participate in their process of learning MF concepts and presented in the results evidence of more meaningful learning, such as interest of the students for the solution of the problem and the choice of potentially significant materials.